ASSESSMENT OF SPATIAL VARIABILITY OF AVAILABLE NUTRIENTS IN POTATO GROWING POCKETS OF AGRA DISTRICT OF UTTAR PRADESH - Kumar, Sushil (Potato Journal, 2019)
Potato J (2018) 45 (2): 131-139ASSESSMENT OF SPATIAL VARIABILITY OF AVAILABLE NUTRIENTS IN POTATO GROWING POCKETS OF AGRA DISTRICT OF UTTAR PRADESHSushil Kumar1, MK Jatav2, VK Dua1 and Shashi Rawat1ABSTRACT: Understanding of spatial variability of soil properties is important in precision agriculture. The present study on spatial variability in available N, P, K and DTPA extractable micronutrients (Zn, Fe, Cu, and Mn) as well as organiccarbon (OC) and soil pH was carried out in Agra (the major potato producing district of Uttar Pradesh) in order. A total of two hundred and fifty six (256) soil samples were collected in a systematic grid design using geographical positioningsystem (GPS). The maps showing the spatial variability of macro and micro nutrients were generated using GIS software (Arc GIS- 9.1). Values of different parameters (like pH, OC, available N, P and K and micronutrients) were linked withcorresponding coordinates and interpolated using IDW technique in Arc GIS 9.1 version. The pH of 70.6% area was recorded between 7.5-8.5 whereas, 28.2% area lies between 8.5- 9.5. The whole area under study was low in organic carbonand available nitrogen. About 12.8% area under potato growing pockets of Agra district was low in available P, whereas 87.2% area was in medium range. About 7.2% area was medium in available potassium, whereas more than 92.8% of areaunder potato was low in available potassium. Among the micronutrients, zinc was the most deficient (39.4% area) in potato grown areas of Agra followed by iron (32.9%), copper (12%) and manganese (7.8%). The spatial variability mapsclearly showed the specific locales, where attention is required with respect to management of macro and micronutrients.